Underwater Acoustics and Depth Uncertainties In the Tropics - Anejionu, O.; Ojinnaka, O. (The International Hydrographic Review, 2011)
Acoustic velocity is known to vary with temperature, depth and salinity (TDS). Calibration of acoustic systems is required at the beginning and end (and sometimes midway) of each hydrographic operation, in order to correct for these velocity variations. Estuarine waters in the tropics were investigated employing wide combinations of temperature, depth and salinity to verify the relationships between these parameters and the acoustic velocity. A maximum error in depth of 0.2m was obtained. Consequently, in the absence of other sources of errors, acoustic systems may need to be calibrated only once in the cause of a full day bathymetric survey operation in the tropics.